Long non-coding RNA SAMMSON as a novel potential diagnostic and prognostic biomarker for oral squamous cell carcinoma - Xijiao Zheng; Xia Tian; Qiao Zhang; Ping Shi; Shu Li (Elsevier, 2020)
Background/purpose: Oral squamous cell carcinoma (OSCC) is one of the most lethal malignancies which accounts for approximately 90% of all malignant oral tumours. SAMMSON is a lncRNA located on chromosome 3p13-3p14 and is known to act as an oncogene in several malignancies. However, its expression and clinical significance in oral squamous cell carcinoma (OSCC) remain mostly unclear. In this study, we investigated the expression and clinical relevance of lncRNA SAMMSON in human OSCC. Materials and methods: Human OSCC cell lines (Tca8113, SCC9, SCC25, CAL27, HN12, HSU3, FADU) and a human normal oral keratinocyte cell line (HNOK) were used to detect the difference of SAMMSON expression. A total of 90 OSCC patients confirmed by pathological and clinical diagnoses at the Hospital of Stomatology, Department of Periodontology, Shandong University were enrolled. The mRNA expression level was analyzed by reverse transcription PCR (QRT-PCR). Statistical analyses including Student's t-test, chi-square method, Kaplan-Meier method, Univariate and, Multivariate Cox regression analysis were performed to analyse all data. Results: This study showed that the expression of SAMMSON was significantly increased in OSCC tissues and cell lines. High SAMMSON expression was significantly associated with TMN stage, tumour differentiation, lymph node metastasis distant metastasis and neighboring tissue infiltration. Patients with high expression of SAMMSON had poor overall survival and disease-free survival compared to those with low levels. Cox regression analysis showed that SAMMSON could act as an independent prognostic factor in OSCC. Conclusion: Serum SAMMSON expression was associated with tumour SAMMSON expression. ROC curve analysis indicated the high diagnostic sensitivity and specificity of serum SAMMSON expression in OSCC patients as compared to other traditional serum biomarker SCCA, TSGF, and CEA. These results indicated that SAMMSON might play an essential role in OSCC progression and could serve as a novel prognostic and diagnostic biomarker in OSCC.